Optimalisasi Pengelolaan Bantuan Rumah Dhuafa dengan Perancangan Sistem Informasi Terintegrasi - Jannah, Miftahul; Haikal, Muhammad; Ahmad, Lukman (Jurnal Manajemen Sistem Informasi (JMASIF), 2024)
This research aims to design an information system for managing assistance for underprivileged houses using a Visual Basic 6.0 application. The application is designed to simplify the management of recipient data, aid distribution, and related reports, focusing on ease of use and time efficiency. The developed system is expected to replace manual methods, which are often time-consuming and prone to errors. The research approach involves system design and development, with stages including planning, data collection, development, and application evaluation. Data were collected through literature study, interviews with social organization managers, field observations, and questionnaires from end-users. The system was developed using Visual Basic 6.0 and Microsoft Access as the database. After the application was completed, testing was conducted to ensure the system functioned as expected, focusing on functionality, data access speed, and user-friendliness. System evaluation showed that the application improved the accuracy and transparency of aid management. This research provides a practical solution for managing assistance for underprivileged houses more efficiently and accountably.